Das lukanische Doppelwerk Zur literarischen Basis frühchristlicher Geschichtsdeutung - Backhaus, Knut (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft, 2022)
Luke-Acts is not a consistent book, but a much-discussed problem. This study presents its discourse history from the eighteenth century to the present, traces its ancient reception, examines the relationship between Luke's writings, the unity of the author, the site of the Luke-Acts in the Marcion debate, its media innovations, and the role it played in shaping the early Christian view of history.